Biliary Duct Injuries Due to Laparoscopic Cholecystectomy: 7-Year Experience at Shahid Modarres Hospital, Tehran, Iran - MalekpourAlamdari, Nasser; Gholizadeh, Barmak (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Nowadays, cholecystectomy is the most prevalent elective abdominal surgery in the U.S., with over 750000 operations performed every year. However, laparoscopic cholecystectomy has been reported with 1% to 8% of major complications, including hemorrhage, wound infection, bile ducts and gallbladder damage. Methods: A total of 1970 medical records of patients undergone laparoscopically at Modarres Hospital between 2010 and 2017 were studied in this research. Of them 1185 were female (60.15%) and 785(39.85%) male. A total of 1003(50.9%) patients were presented with cholecystitis, 955(48.5%) with symptomatic cholelithiasis, and 12(0.6%) with polyp. Results: Biliary tract injury was reported in 11 cases, complete cut off of Common Bile Duct (CBD) in 4(0.2%) cases (3 males and 1 female), partial CBD injuries in 3 cases (2 males and 1 female), complete closure of CBD in 1 female case, and partially closure of CBD by clips in 3(0.1%) cases (1 male and 2 female). Conclusion: The laparoscopic method seems to be the ideal method of cholecystectomy, not just because of its cosmetic reasons, also due to its less invasive procedure.